Penggunaan Media Pembelajaran Papan Huruf dalam Mengenalkan Huruf pada Anak di TK Libukang Permai Kota Palopo - Debi, Debi Melani Putri F; Munir Yusuf; Hasis, Pertiwi Kamariah (Universitas Muhammadiyah Metro, 2025)
The ability to recognize letters in group B at Libukang Permai Kindergarten, Palopo City is still low, there are still some children who do not know letters and cannot distinguish letters. The ability to recognize letters will of course have a negative impact on the person concerned because the impact will be greatly felt when entering the next level of education. The type of research used is Classroom Action Research (CAR) with the Kurt Lewin Model which consists of two cycles. Cycle I consists of 4 meetings and cycle II consists of 4 meetings. Each cycle includes the planning, implementation, observation and reflection stages. The subjects of this study were students of Libukang Permai Kindergarten in the 2024/2025 academic year totaling 12 children, namely 5 boys and 7 girls. The actions implemented, namely the letter board media to introduce letters to children, were obtained from the results of observations, interviews and documentation analyzed using quantitative and qualitative descriptive. The success criteria for this study were determined if the child got a score of 80% of all indicators. The results of this study indicate that the application of the Letter Board Media is in accordance with the needs of children and the use of the Letter Board Media can introduce letters to children. The score in the pre-action condition was 40% of all indicators with the category Not Yet Developing (BB). Cycle I with an observation score of 54% of all indicators with the category Starting to Develop (MB). Cycle II with a score of 82% of all indicators with the category Developing Very Well (BSB). Thus, this Classroom Action Research (CAR) is said to be successful so that researchers recommend learning using Letter Board Media in introducing letters to children. Letter Board Media makes learning more interactive and interesting.